2021
DOI: 10.1111/1753-6405.13125
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of unintentional injury among children in New Zealand: a systematic review

Abstract: Objective: To identify contemporary studies investigating multifaceted and inter‐linked contributory frameworks for unintentional injuries among children in New Zealand. Methods: A literature review was performed in seven databases. Studies published in English up to February 2020 reporting risk factors for child injury in New Zealand were included. Eligible study designs included: cohort, case‐control and case‐crossover studies. The quality of studies was assessed using the GATE frame tool. The PRISMA (Prefer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 48 publications
2
7
0
Order By: Relevance
“…They are mainly defined by children's individual factors such as age, sex, psychological factors and behavioural factors, then by social and financial factors of the family, but also by other factors in the child's social environment. 26 Evaluating the risk factors, a significant correlation between age and unintentional injuries was found and the occurrence of unintentional injuries increased with the children's age, which is in accordance with previous studies. 25,26 First, according to authors' knowledge this is the first study in the Republic of Srpska, Bosnia and Herzegovina that examined the characteristics of unintentional injuries in children and adolescents treated in EMS.…”
Section: Strengths and Limitationssupporting
confidence: 91%
See 1 more Smart Citation
“…They are mainly defined by children's individual factors such as age, sex, psychological factors and behavioural factors, then by social and financial factors of the family, but also by other factors in the child's social environment. 26 Evaluating the risk factors, a significant correlation between age and unintentional injuries was found and the occurrence of unintentional injuries increased with the children's age, which is in accordance with previous studies. 25,26 First, according to authors' knowledge this is the first study in the Republic of Srpska, Bosnia and Herzegovina that examined the characteristics of unintentional injuries in children and adolescents treated in EMS.…”
Section: Strengths and Limitationssupporting
confidence: 91%
“…26 Evaluating the risk factors, a significant correlation between age and unintentional injuries was found and the occurrence of unintentional injuries increased with the children's age, which is in accordance with previous studies. 25,26 First, according to authors' knowledge this is the first study in the Republic of Srpska, Bosnia and Herzegovina that examined the characteristics of unintentional injuries in children and adolescents treated in EMS. Second, the major strength were and the robust sample size.…”
Section: Strengths and Limitationssupporting
confidence: 91%
“…The study revealed no statistically significant difference between the sociodemographic characteristics of the case and control group. Studies have shown that poor socioeconomic status, number of children, young mother age, and being a single parent are associated with unintentional injuries (Ghebreab et al., 2021; Moshiro et al., 2021). This may be due to the characteristics of the sample and regional/cultural differences.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the studies (Campbell et al., 2019; Henery et al., 2021; Shi et al., 2015) and prevention efforts, injuries continue to affect children, and mortality and morbidity rates are high. In addition, there are a limited number of case‐control studies (Ghebreab et al., 2021; Zhang et al., 2021) conducted to determine the risk factors and maternal attitudes associated with unintentional injuries in children. This study may contribute to a better understanding of the risk factors associated with unintentional injuries in children and to take precautions against them.…”
Section: Introductionmentioning
confidence: 99%
“…There have been numerous descriptive reports and studies in NZ using conventional epidemiological methods to investigate risk factors for unintentional childhood injury 9 16–18. These studies have predominantly focused on short-term, single or a few exposures despite the likely complex, multifaceted and interlinked contributory frameworks to childhood injury 19 20. These studies have highlighted several important modifiable risk factors.…”
Section: Introductionmentioning
confidence: 99%